Biorefinery : from biomass to chemicals and fuels - Aresta, Michele, 1940-; Dibenedetto, Angela; Dumeignil, Franck ([Walter] de Gruyter, 2012)
"This book provides an introduction to the basic science and technologies for the conversion of biomass (terrestrial and aquatic) into chemicals and fuels, as well as an overview of innovations in the field. The entire value chain for converting raw materials into platform molecules and their transformation into final productsare presented in detail. Both cellulosic and oleaginous biomassare considered. The book contains contributions by both academic scientists and industrial technologists so that each topic combines state-of-the-art scientific knowledge with innovative technologies relevant to chemical industries."